Patterning 2D Organic Crystalline Semiconductors via Thermally Induced Self‐Assembly. (16th August 2020) - Duan, Yiwei; Qian, Jun; Guo, Jianhang; Jiang, Sai; Yang, Chengdong; Wang, Hengyuan; Wang, Qijing; Shi, Yi; Li, Yun
Abstract: Fabricating 2D organic crystalline semiconductors (2DOCSs) in a patterned structure is an essential prerequisite for application toward large‐scale and high‐throughput manufacturing integrated devices. However, the deposition of 2DOCS arrays with structural perfection and thickness control through suitable solution‐based techniques remains challenging. Here, a promising patterning technique is proposed for high‐quality 2DOCS arrays with centimeter‐scale size and tunable molecular layer number via thermally induced self‐assembly (TISA). The achieved 2DOCS arrays exhibit superior carrier mobility and reliable performance uniformity. Field‐effect transistors yield maximum and average carrier mobilities of 13.40 and 9.21 cm 2 V −1 s −1, respectively. Furthermore, constructed vertical molecular heterostructure‐based planar diode arrays exhibit high electrical rectification (rectifying ratio of ≈10 4 ), gate tunability, and fast photoresponse speed. Therefore, the work paves the way toward rational design and construction of organic device arrays for high‐performance organic integrated circuits. Abstract : A patterning method to fabricate high‐quality 2D organic crystalline semiconductor (2DOCS) arrays with centimeter‐scale size and tunable molecular layer number is demonstrated. The achieved 2DOCS arrays exhibit superior carrier mobility and reliable performance uniformity. These investigations on solution‐grown 2DOCS arrays can promote precise morphology control of other 2D ultrathin organic functional films and the realization of novel organic electronics.